Development of a Website-Based Accounting Information System at Balaram Mangrove Heroes Ecotourism, Tanjung Benoa - Anak Agung Gede Krisna; Ni Ketut Lita Patma Dewi; Ni Kadek Kristina Yanti; Ni Luh Riska Yusmarisa; I Putu Arnawa; Ni Ketut Mareni (Transpublika Publisher, 2026)
Balaram Mangrove Heroes Tanjung Benoa Ecotourism faces problems in financial management that is still carried out manually, thus potentially causing recording errors, data loss, and delays in the preparation of financial reports. This study aims to develop a website-based accounting information system to improve the effectiveness, accuracy, and transparency of financial management. This study uses a qualitative method with data collection techniques in the form of interviews, observation, and documentation. Data analysis was carried out descriptively to identify problems and system requirements. The results of the study indicate that the manual recording system causes inefficiency, a high risk of human error, and the unavailability of structured financial reports. Therefore, a website-based accounting information system named ECOFIN was developed, which is capable of recording transactions automatically, storing data in an integrated manner, and generating financial reports in real-time. System testing conducted through functional verification confirmed that all core features of ECOFIN, including ticket sales recording, commission and expense management, and automatic generation of profit and loss statements and balance sheets, operated in accordance with the designed system requirements. Based on these functional test results, the implementation of the ECOFIN system demonstrates improvement in the efficiency, accuracy, and transparency of financial management and supports data-based decision making in ecotourism management.